Lucas Cranach the Elder. Painting materials, techniques and workshop practice - Gómez González, Marisa (Ge-conservacion, 2011)
Reseña del libro: Lucas Cranach the Elder. Painting materials, techniques and workshop practice Gunnar Heydenreich Editorial Amsterdam University Press Amsterdam, 2007 464 páginas, 277 figuras, 25 x 19 cm. ISBN: 13 978 90 53356 7456